Deficiency in DNA damage response, a new characteristic of cells infected with latent HIV-1. Issue 10 (19th May 2017) - Piekna-Przybylska, Dorota; Sharma, Gaurav; Maggirwar, Sanjay B.; Bambara, Robert A.
ABSTRACT: Viruses can interact with host cell molecules responsible for the recognition and repair of DNA lesions, resulting in dysfunctional DNA damage response (DDR). Cells with inefficient DDR are more vulnerable to therapeutic approaches that target DDR, thereby raising DNA damage to a threshold that triggers apoptosis. Here, we demonstrate that 2 Jurkat-derived cell lines with incorporated silent HIV-1 provirus show increases in DDR signaling that responds to formation of double strand DNA breaks (DSBs). We found that phosphorylation of histone H2AX on Ser139 (gamma-H2AX), a biomarker of DSBs, and phosphorylation of ATM at Ser1981, Chk2 at Thr68, and p53 at Ser15, part of signaling pathways associated with DSBs, are elevated in these cells. These results indicate a DDR defect even though the virus is latent. DDR-inducing agents, specifically high doses of nucleoside RT inhibitors (NRTIs), caused greater increases in gamma-H2AX levels in latently infected cells. Additionally, latently infected cells are more susceptible to long-term exposure to G-quadruplex stabilizing agents, and this effect is enhanced when the agent is combined with an inhibitor targeting DNA-PK, which is crucial for DSB repair and telomere maintenance. Moreover, exposing these cells to the cancer drug etoposide resulted in formation of DSBs at a higher rate than in un-infected cells. Similar effects of etoposide were also observed in population of primary memory T cells infected with latent HIV-1. Sensitivity to these agents highlights a unique vulnerability of latently infected cells, a new feature that could potentially be used in developing therapies to eliminate HIV-1 reservoirs.